Effect of Activated Human Protein C on Disseminated Intravascular Coagulation Induced by Lipopolysaccharide in Rats - Aoki, Yasunori; Ota, Mikio; Katsuura, Yasuhiro; Komoriya, Keiji; Nakagaki, Tomohiro (Arzneimittelforschung, 2000)
Protein C is the zymogen of an anticoagulant serine protease and is converted to its active form (activated protein C: APC) by thrombin in the presence of thrombomodulin. APC plays an important role in regulating coagulation and fibrinolysis by inactivating not only blood coagulation factors Va and VIIIa but also type-1 plasminogen activator inhibitor (PAI-1).The aim of the present study was to examine the effect of a human APC product (designated as CTC-111), compared with that of heparin, on the disseminated intravascular coagulation (DIC) induced by lipopolysaccharide (LPS) in rats. LPS (1 mg/kg/h) infusion was performed through a femoral vein for 4 h. One-fifth amount of the total dosage of CTC-111 or heparin was injected into the other femoral vein, followed by a 4-h infusion of the remainder.Both CTC-111 (10 000-100 000 U/kg) and heparin (400-800 IU/kg) inhibited the decrease in platelet count and fibrinogen level equally. The prolonged activated partial thromboplastin time and prothrombin time observed in DIC rats were further elongated in both CTC-111-and heparin-treated rats. But, this prolongation was less in CTC-111-treated rats than in the heparin-treated ones. Heparin inhibited the increase in fibrin and fibrinogen degradation products more prominently than CTC-111. On the other hand, CTC-111 strongly inhibited the increase in PAI-1 activity but heparin did not. These results suggest that CTC-111 may enhance fibrinolysis through its direct inhibitory effect on PAI-1.The parameters for liver or renal damage, i.e., plasma glutamic-oxaloacetic transaminase (GOT), glutamic-pyruvic transaminase (GPT), creatinine (Cre) and blood urea nitrogen (BUN), were significantly increased by LPS infusion. Both CTC-111 (100 000 U/kg) and heparin (800 IU/kg) decreased the increase in GOT and GPT levels significantly, whereas neither affected the increase in Cre or BUN. From these results, the activation of the blood coagulation system might partially contribute to the progression of liver damage caused by LPS, and might be less involved in the progression of renal damage in this model.In conclusion, CTC-111 showed both anticoagulant and profibrinolytic activity in the LPS-induced DIC model without excessive prolongation of coagulation time. From these results, CTC-111 is expected to be a useful remedy for DIC without the risk of bleeding.
Keywords: Activated protein C, effect on disseminated intravascular coagulation, rat, tissue damage; CTC-111; Lipopolysaccharide; Plasminogen activator inhibitor